Benthic meltwater fjord habitats formed by rapid glacier recession on King George Island, Antarctica. (14th May 2018) - Jerosch, Kerstin; Pehlke, Hendrik; Monien, Patrick; Scharf, Frauke; Weber, Lukas; Kuhn, Gerhard; Braun, Matthias H.; Abele, Doris
Abstract : The coasts of the West Antarctic Peninsula are strongly influenced by glacier meltwater discharge. The spatial structure and biogeochemical composition of inshore habitats are shaped by large quantities of terrigenous particulate material deposited in the vicinity of the coast, which impacts the pelagic and benthic ecosystems. We used a multitude of geochemical and environmental variables to identify the radius extension of the meltwater impact from the Fourcade Glacier into the fjord system of Potter Cove, King George Island. The k -means cluster algorithm, canonical correspondence analysis, variance analysis and Tukey's post hoc multiple comparison tests were applied to define and cluster coastal meltwater habitats. A minimum of 10 clusters were needed to classify the 8 km 2 study area into meltwater fjord habitats (MFHs), fjord habitats and marine habitats. Strontium content in surface sediments is the main geochemical indicator for lithogenic creek discharge in Potter Cove. Furthermore, bathymetry, glacier distance and geomorphic positioning are the essential habitats explaining variables. The mean and maximum MFH extent amounted to 1 km and 2 km, respectively. Extrapolation of the identified meltwater impact ranges to King George Island coastlines, which are presently ice-covered bays and fjord areas, indicated an overall coverage of 200–400 km 2 MFH, underpinning the importance of better understanding the biology and biogeochemistry in terrestrial marine transition zones. This article is part of the theme issue 'The marine system of the West Antarctic Peninsula: status and strategy for progress in a region of rapid change'.